Can Transportation Change Land Property Rights in Developing Rural Areas? Case Study of Land Titles in a Brazilian Municipality. Issue 5 (May 2019) - de Oliveira Alves, Lucas Bispo; Maeda, Shinnosuke; Morikawa, So; Kato, Hironori
The impact of transportation on economic development has been the subject of intense research. This paper investigates a potential impact on yet another aspect of the economy: land property rights (LPR). This institution determines who may own land and under what circumstances land transactions happen, with significant implications for farmers' incentives and agricultural performance. Transportation is assumed to represent a technological shock capable of generating incentives for land titling. Data was collected in a rural municipality in Brazil where agricultural development has been closely related to the construction of a railway and a paved road. Farmers have subsequently applied for land titles. Two hypotheses are tested: first, farmers whose produce is transported by the railway are more likely to have land titles than those whose produce is not; second, farmers that are located closer to the paved road are more likely to have land titles than those located further away. IV are introduced to treat anticipated endogenous problems. Results indicate the acceptance of both hypotheses, which points to one significant policy implication: improvements in LPR can be considered one indirect impact of transportation, at least where the legal framework for titling is present. Initiatives to improve transportation and LPR may be implemented in parallel with mutually reinforcing effects. It must be noted, however, that likelihood of titling in rural areas is dependent on modes of transportation and on which products can be produced according to the agro-ecological features of each region.